Studying the pathogenic role of catecholamines in the development of retinopathy of prematurity on an experimental model of the disease - L. A. Katargina; N. A. Osipova; A. J. Panova; N. S. Bondarenko; Yu. O. Nikishina; A. R. Murtazina; M. V. Ugryumov (Российский офтальмологический журнал)
Purpose. To study the involvement of dopamine and noradrenaline in the pathogenesis of retinopathy of prematurity (ROP) on an original rat model of the disease.Material and methods. The study was conducted on 41 newborn Wistar rats (82 eyes), divided into 2 groups: experimental (EROP, rats with experimental ROP, n = 21) and control (n = 20). The rats were taken out of the experiment on the 7th, 14th, 23rd and 28th days of life. All rat pups were given binocular enucleation at the indicated times, whereupon the eyeballs were dissected along the limbus and the cornea, lens, hyaloid system, and vitreous were removed. The retina was isolated from the eye cup. The isolated retinal samples were homogenized in 10 volumes of 0.1 n HClO4 containing 50 pmol/ml (or more) of 3,4-dihydroxybenzylamine (DBA), using an ultrasonic homogenizer (Labsonic M, Sartorius), centrifuged at 2000g for 20 minutes, and the norepinephrine, dopamine and precursor of dopamine — L-3,4 dihydroxyphenylalanine (L-DOPA) were determined in the resulting supernatant. The contents of substances were measured using reverse phase high performance liquid chromatography with electrochemical detection (Amperometric detector LC-4B, Bioanalytical Systems, USA) set at the potential of 850 mV.Results. On the 7th day, on which avascular retinal zones in both groups of animals existed, no significant differences were found in the content of monoamines in the retina of rats with EROP and in the control group. On the 28th day, the content of noradrenaline, dopamine and L-DOPA in the retina of the experimental group was significantly increased compared with the control. On day 23, corresponding to the peak of neovascularization in the EROP model applied, the level of norepinephrine in the retina of experimental group rats was significantly higher, while the level of L-DOPA was significantly lower compared to the control group. The dopamine level was comparable in both study groups and similar to the level of L-DOPA in the control group. On the 28th day, corresponding to the beginning of EROP regression accompanied by vascular activity decrease, the content of dopamine and L-DOPA remained lower than in the control group.Conclusion. During the development of pathological neovascularization of rat pup retina with EROP, the level of noradrenaline is growing, revealing a peak corresponding to the period of pronounced pathological growth of retinal vessels within the applied model, which indicates to the fact of noradrenalin proangiogenic properties and its direct participation in the pathogenesis of ROP. The level of dopamine and its predecessor, L-DOPA, increased towards the 14th day as compared to its level detected on the 7th day, which may be due to the maturation of the amacrine cells producing, and then, on the day 23. i. e. during the period corresponding to the maximum peak of angiogenesis, its relative decrease of L-DOPA was noted. It can be assumed that the lack of this monoamine, and hence insufficient manifestation of its anti-angiogenic properties contributes to the development of uncontrolled neovascularization of the retina.